Attachment‐Related Biases in Adolescents' Memory. Issue 6 (14th July 2014) - Dykas, Matthew J.; Woodhouse, Susan S.; Jones, Jason D.; Cassidy, Jude
<x xml:space="preserve">Abstract</x> Attachment theorists propose that individuals' internal working models influence their social information processing. This study explored links between attachment representations and social information processing by examining adolescents' (n = 189; Mage = 16.5 years) attachment‐related memory biases. Participants completed laboratory tasks assessing memory for (a) emotionally salient childhood events, (b) adjectives describing their parents, and (c) generalized parent‐related characteristics not specific to their own parents. As expected, dismissing attachment (assessed using the Adult Attachment Interview) was linked across tasks to a deactivating strategy in which memory for emotional childhood events and attachment‐relevant stimuli was reduced. In contrast, evidence that preoccupied attachment was linked to a hyperactivating strategy in which memory was heightened emerged only in relation to emotional childhood events.